Handling asphalt, Pitch Lake, Trinidad, B.W.I. - (:unkn) unknown (My University, 2010)
Photo of blue collar workers digging pitch and loading it onto railroad carts. No.25584
Colour: Blue, Green, Red and Brown Hues; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Asphalt industry--Trinidad and Tobago; Pitch; Carriages and carts--Trinidad and Tobago; Railroad cars--Trinidad and Tobago; Blue collar workers--Trinidad and Tobago; Railroads--Trinidad and Tobago; Pitch Lake, The (La Brea)